Ragam Pemahaman Kristologi: Telaah Teologis dalam Konteks Alkitab - Fitri Fitri; Triani Cahya Ningsih; Prita Aura Eklesia; Yuce Eviona Yapen; Sarmauli Sarmauli (Jurnal Silih Asuh : Teologi dan Misi, 2025)
The understanding of Jesus Christ in the Bible is very diverse and is reflected in the various titles given to Him. Each title used by the biblical authors indicates a certain aspect of Jesus' identity and mission according to their historical and theological context. This research is a qualitative research using the literature study method. This research was conducted to analyze the Diversity of Christological Experiences in the Bible.